The business of telehealth - Krishnan Ganapathy (Apollo Medicine, 2022)
The author has been actively involved in the successful management of a number of small and mega telehealth projects. This communication summarizes the importance of management science in addressing operational, technical, and clinical challenges in virtually reaching the unreached. These are seldom discussed. Publications dealing with organizational, regulatory, and cultural issues vis a vis its deployment in initiating, sustaining, and making viable telehealth activities have been reviewed. The WHO framework for the implementation of telemedicine services gives some guidelines. This article reflects personal experience, from discussions with the author's street-smart team. The latter's approach fitted in with the dicta of management gurus. A detailed need assessment study was the first step. Risks in program implementation, challenges in providing teleconsultants, and the necessity for training, retraining, learning, relearning, and unlearning are emphasized. Identifying champions in the community and team and making the project self-sustaining is critical. Future-ready access to cost-effective, need-based, appropriate technology including a robust telecommunication network is vital. Patient perspectives of telemedicine quality must be considered. Measurable, reproducible, objective parameters to quantify success need to be defined. Barriers need to be foreseen and addressed. Legal, regulatory, and security issues have to be complied with. Cultural transformation is necessary for the acceptance of technology-enabled remote virtual health care. Urban teleconsultants need to be sensitized for community interaction while deploying cutting-edge technology. Identifying opportunities to initiate telehealth activities, implementation challenges, and adoption of pandemic-associated specific strategies are discussed.